Selling a lifestyle: A representation study of Kylie Jenner’s cosmetic advertisements - Vinka Fatkhania Salisa; Krisna Sujiwa (COMMICAST, 2026)
This study examines how Kylie Jenner’s advertisements construct and disseminate meanings of beauty, luxury, and motherhood through Stuart Hall’s representation theory. Using qualitative document analysis of two YouTube advertisements Kylie Lip Kit and Kylie Baby the research applies Hall’s encoding/decoding model within a postmodern framework to analyze how visual and narrative strategies shape audience interpretation. The findings show that Jenner’s self–representation operates at the intersection of euthenics and commodification, transforming beauty and motherhood into aspirational consumer identities. Her branding reinforces neoliberal discourses of self – reinvention and feminine subjectivity in digital culture. This study extends Hall’s representation theory into the domain of influencer driven brand culture, highlighting how celebrity entrepreneurship reconfigures cultural symbols within social media advertising. This research offers a novel extension of representation theory by situating celebrity motherhood within the political economy of influencer driven luxury branding.